1999
DOI: 10.2116/analsci.15.433
|View full text |Cite
|
Sign up to set email alerts
|

Selective Flotation-Spectrophotometric Procedure for the Trace Analysis of Palladium(II) in Different Matrices

Abstract: The determination of palladium under microgram concentration levels is generally hampered by insufficient sensitivity of the techniques used and or by a matrix effect. With the introduction of techniques, sensitivity problems have been drastically reduced.There are chemical and physical methods to increase the sensitivity and decreasing matrix effects, such as extraction 1,2 or preconcentration by solvent evaporation; however, in the presence of complex matrices with very low concentration of the analyte, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…In addition, the viscosity of the surfactant-rich phase increases, leading to poor sensitivity. 34,35 At lower CTAB concentrations (below 0.005% w/v), the preconcentration efficiency of the complex was very low, probably due to assemblies that were inadequate to quantitatively entrap the hydrophobic complex and float the complex. …”
Section: Type and Amount Of Surfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the viscosity of the surfactant-rich phase increases, leading to poor sensitivity. 34,35 At lower CTAB concentrations (below 0.005% w/v), the preconcentration efficiency of the complex was very low, probably due to assemblies that were inadequate to quantitatively entrap the hydrophobic complex and float the complex. …”
Section: Type and Amount Of Surfactantmentioning
confidence: 99%
“…Many factors influence to perform a proper flotation, but an important role has the collector with its colloid nature. [30][31][32][33][34] According to our knowledge there is still not reported any method in the literature, based on the simultaneous flotation of transition and heavy metal ions using Schiff's bases ligand. Therefore, in detail it was decided to develop an efficient method for the extraction and preconcentration of trace amounts of some metal ions from aqueous media using bis(2-hydroxyacetophenone)-1,4-butanediimine (BHABDI) and determination by FAAS.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] Consequently, such a process enabled and facilitated the spectrophotometric determination of the analyte.…”
Section: Flotation-separation Of V(iv)mentioning
confidence: 99%
“…On the other hand, methods for the separation and preconcentration of metals by flotation, followed by their spectrophotometric determination, have increased in popularity in recent years. [9][10][11][12][13][14][15][16][17][18] A literature survey showed that ion-flotation followed by spectrophotometric determination of V(IV) is rarely reported. 19 Also, no attempt has been found for using 1-(2-hydroxy-4-methoxybenzophenone)-4-phenylthiosemicarbazone (HMBPT) in this concern.…”
mentioning
confidence: 99%
“…Among several preconcentration techniques, interactions based on chelate formation have received considerable attention due to their simplicity and ability to attain high enrichment factor [17,18]. Much attention has been given to the preconcentration and separation of heavy metals from environmental, biological and pharmaceutical samples by flotation techniques [19][20][21][22][23][24]. In this respect, the adoption of a flotation methodology has been shown to give accurate and reproducible results, together with simple, rapid analytical processing and low chemical blanks.…”
Section: Introductionmentioning
confidence: 99%